Comparative Two-dimensional Gel Electrophoresis Maps for Amastigote-like Proteomes of Iranian Leishmania Tropica and Leishmania major Isolates: - Ashrafmansouri, Marzieh; Sadjjadi, Fatemeh Sadat; Seyyedtabaei, Seyyedjavad; Haghighi, Ali; Rezaei-Tavirani, Mostafa; Ahmadi, Nayebali (Galen Medical Journal, 2019)
Background: Leishmania major and Leishmania tropica are the main causative agents of cutaneous leishmaniasis. Proteomics as a novel approaches could be used to evaluate protein expression levels in different stages of Leishmania species. We compare the protein contents of amastigote-like forms in L. tropica and L. major using two-dimensional gel electrophoresis (2-DE) and bioinformatics methods. Materials and Methods: Leishmania parasites were isolated from the lesions of Iranian patients and identified using restriction fragment length polymorphism-polymerase chain reaction (RFLP-PCR). Five isolates of each two species were cultured in specific media to obtain amastigote-like forms to be prepared for proteomics study. Total protein contents were separated using 2-DE. The gels were stained by silver nitrate and scan was imaged. The protein spots with different expression changes in each gel were analyzed using Progenesis SameSpots software. Results: A total of 354 protein spots were detected in both amastigote-like forms. Comparative analysis of protein spots with different expressions in the two amastigote-like form species showed 173 highly expressed spots of which 74 L. tropica and 99 L. major proteins were spotted with foldâ‰¥2. Also, 16 and 20 new protein spots were uniquely found in L. tropica and L. major, respectively. Clustering of different detected proteins using correlation analysis divided the proteins into two clusters based on their expression level. Furthermore, clustering results were confirmed by principal component analysis. Conclusion: Using proteomics methods specially 2-DE and statistical analysis demonstrated significant changes in protein expression levels in amastigote-like forms of L. tropica and L. major isolates.Â  [GMJ.2019;8:e1520]